2013
DOI: 10.3109/09637486.2013.775224
|View full text |Cite
|
Sign up to set email alerts
|

The effects of synbiotic supplementation on some cardio-metabolic risk factors in overweight and obese children: a randomized triple-masked controlled trial

Abstract: Recent studies have suggested some beneficial effects of probiotics on controlling excess weight in adults; such experience is limited in the pediatric age group. This study aimed to assess the anti-obesity and lipid-lowering effects of a synbiotic supplement among children and adolescents. We conducted a randomized triple-masked controlled trial among 70 participants aged 6-18 years with body mass index (BMI) equal or higher than 85th percentile. They were randomly assigned to two groups of equal number to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 34 publications
2
61
0
5
Order By: Relevance
“…Rodent studies have shown that the negative metabolic effects of a high-fat diet are dependent on a reduction in the abundance of bifidobacteria [4345]. Indeed, a bifidogenic synbiotic has been shown to reduce weight in overweight children [46]. Obesity and high-fat diets induce endotoxemia, an increase in the level of circulating lipopolysaccharide (LPS), which appears to be a requirement for the associated metabolic consequences [39, 43, 46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent studies have shown that the negative metabolic effects of a high-fat diet are dependent on a reduction in the abundance of bifidobacteria [4345]. Indeed, a bifidogenic synbiotic has been shown to reduce weight in overweight children [46]. Obesity and high-fat diets induce endotoxemia, an increase in the level of circulating lipopolysaccharide (LPS), which appears to be a requirement for the associated metabolic consequences [39, 43, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a bifidogenic synbiotic has been shown to reduce weight in overweight children [46]. Obesity and high-fat diets induce endotoxemia, an increase in the level of circulating lipopolysaccharide (LPS), which appears to be a requirement for the associated metabolic consequences [39, 43, 46]. Bifidobacteria may reduce systemic inflammation by reducing the abundance of inflammatory LPS-producing bacteria [45], by up-regulating tight-junction proteins in the gut and thus reducing the leakage of LPS and other bacterial antigens into the circulation [43, 47], and by stimulating regulatory T cells and the production of anti-inflammatory cytokines [45].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that synbiotic supplementation reduces LDL levels. Safavi et al (27) showed a significant difference in all lipid parameters after 8 weeks of synbiotic supplementation in obese children. In contrast, Ipar et al (28) found significant improvement only in TC and LDL levels and not in TG levels after synbiotic supplementation, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Ähnliche Resultate wurden von Famouri et al berichtet, die 64 Kinder mit Adipositas und NAFLD doppelblind randomisiert einer Placebo-oder einer Interventionsgruppe zuwiesen (Lactobacillus acidophilus, Bifidobacterium lactis, Bifidobacterium bifidum, Lactobacillus rhamnosus, [7]). Ein günstiger Effekt von mehreren Bakterienstämmen (Lactobacillen und Bifidobakterien) in Kombination mit Fructooligosacchariden auf den BMI-Z-Score und den Bauchumfang ("Synbiotikum") wurde außerdem in einer doppelblinden randomisierten [32] bzw. einer offen randomisierten Studie an Kindern mit Adipositas berichtet [15].…”
Section: Bakterielle Metaboliten Und Adipositasunclassified